1993
DOI: 10.1557/jmr.1993.1179
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nylon 6-clay hybrid

Abstract: It was found that montmorillonite cation exchanged for 12-aminolauric acid (12-montmorillonite) was swollen by ∊-caprolactam to form a new intercalated compound. Caprolactam was polymerized in the interlayer of montmorillonite, a layer silicate, yielding a nylon 6-clay hybrid (NCH). The silicate layers of montmorillonite were uniformly dispersed in nylon 6. The carboxyl end groups of 12-aminolauric acid in 12-montmorillonite initiated polymerization of ∊-caprolactam, and as 12-montmorillonite content became la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
1,392
2
28

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 2,130 publications
(1,432 citation statements)
references
References 1 publication
10
1,392
2
28
Order By: Relevance
“…Such properties are related to the volume fraction, shape and size of the filler particles. Following the pioneering work of Toyota researchers on a nylon 6-clay nanocomposite in the early 1990s [43,47,48], well-exfoliated nanocomposites have been produced in various nylons [44,[49][50][51], polystyrene [52], certain polyimides [53], polypropylene [54][55][56][57], polylactide [58,59] and epoxies [60][61][62]. These studies showed that the improvement in the mechanical performances of nanocomposites mainly originated from the nanosize dimensions of silicates (as this results in an extremely large aspect ratio) and from strong polymer-filler interactions that might affect the effectiveness of the load transfer between the silicate layers and polymer matrix.…”
Section: Mechanical Properties Of Nanocompositesmentioning
confidence: 99%
“…Such properties are related to the volume fraction, shape and size of the filler particles. Following the pioneering work of Toyota researchers on a nylon 6-clay nanocomposite in the early 1990s [43,47,48], well-exfoliated nanocomposites have been produced in various nylons [44,[49][50][51], polystyrene [52], certain polyimides [53], polypropylene [54][55][56][57], polylactide [58,59] and epoxies [60][61][62]. These studies showed that the improvement in the mechanical performances of nanocomposites mainly originated from the nanosize dimensions of silicates (as this results in an extremely large aspect ratio) and from strong polymer-filler interactions that might affect the effectiveness of the load transfer between the silicate layers and polymer matrix.…”
Section: Mechanical Properties Of Nanocompositesmentioning
confidence: 99%
“…Os HDLs possuem uma estrutura baseada no mineral Brucita (Mg(OH) 2 ), onde parte dos cátions magnésio coordenados octaédricamente à íons hidroxila, são substituídos isomorficamente por cátions trivalentes, gerando um excesso de carga das lamelas, que é compensada pela intercalação de ânions hidratados. Os HDLs possuem uma formula genérica do tipo [M +2 1-x M +3 x (OH) 2 ] x-(A -n ) x/n .yH 2 O, onde M +2 e M +3 representam respectivamente os cátion divalentes e trivalentes da lamela e A -n .…”
Section: Introductionunclassified
“…Os HDLs possuem uma formula genérica do tipo [M +2 1-x M +3 x (OH) 2 ] x-(A -n ) x/n .yH 2 O, onde M +2 e M +3 representam respectivamente os cátion divalentes e trivalentes da lamela e A -n . yH 2 O representa o ânion hidratado intercalado [9] . Uma série de metais pode fazer parte da lamela, embora uma correta combinação entre o cátion divalente e trivalente seja necessária Tipicamente os metais podem ser: M +2 = Mg, Ca, Sr, Mn, Fe, Co, Ni, Cu, Zn, Cd, M 3+ = Al, Cr, Fe, Sc, Ga, Y, In, Ce, além de alguns excessões como M + = Li e M 4+ = Zr, Pd, Sn.…”
Section: Introductionunclassified
See 2 more Smart Citations